The AI Localism Canvas. A Framework to Assess the Emergence of Governance of AI within Cities. - Verhulst, Stefaan; Young, Andrew; Sloane, Mona (Steiner, 2021)
This article examines the emerging field AI Localism – a global move toward innovative governance of AI at the subnational level. The piece introduces the current state of play in the field, and introduces an “AI Localism Canvas” to help decision-makers identify, categorize and assess instances of AI Localism specific to a city or region.
Keywords: Künstliche Intelligenz; Urban Governance; Regional Governance; Entscheidungsfindung; Prozesssteuerung; Planungsinstrument; Stadtentwicklungsplanung